Edge enhancement of IBP reconstruction by using sharp infinite symmetrical exponential filter - A.R. A Nazren; Ngadiran R.; S. N. Yaakob (Institute of Advanced Engineering and Science, 2019)
This study contributes to provide an enhancement technique for improving the Iterative Back Projection (IBP) Super Resolution technique by using the Sharp Infinite Symmetrical Filter (SISEF). Theoretically, the IBP technique operates as minimizer the error reconstruction iteratively until it refined the High Resolution (HR) image. However, due to iterative manner and lack of edge guidance during the back projection operation, this technique has suffered from produced the ringing artefact on the HR image appearances. Additionally, the IBP reconstruction also demands for large number iteration for accomplishing the prediction HR image. This problem arose when the IBP estimator tended to oscillate at the same solution frequently. In order to overcome these constraints, the SISEF is deployed as regulator to improve the IBP estimator with provides an accurate edge information for enhancing the edge image and reduce the ringing artefacts. Fortunately, highly precision of edge information provided by SISEF capable to reduce amount of estimation process repetition.